2021
DOI: 10.1088/1757-899x/1094/1/012109
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis of a Novel Smart Knee Joint Prosthesis for Transfemoral Amputation

Abstract: The absence of a limb impacts devastatingly on any person, especially if it is the lower limb as it is paramount to human locomotion. The effect of mobility loss reduces independence, and affects amputees’ lifestyles. A smart prosthetic knee joint is designed and manufactured in which the amputee above the knee can perform various daily and effective movements. It is distinguished by its distinctive and very high efficiency mechanically and electronically. The new design of the artificial smart knee joint has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The following explains the relationship between the forces produced by the actuator and the torque of the knee joint [6]:…”
Section: Mechanical Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following explains the relationship between the forces produced by the actuator and the torque of the knee joint [6]:…”
Section: Mechanical Componentsmentioning
confidence: 99%
“…However, amputees consume around 60% more energy than others since walking requires the wearer's muscles [5]. A passive prosthesis balances the impedance with a power supply to assist with walking [6][7][8][9]. The user of the active prosthesis has less physical stress than with the passive prosthesis while still being able to walk normally.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Kamel et al [15] modelled and analyzed a prosthesis for use in amputations of transfemoral nature presenting a smart knee joint of novel proportions. The finite element method was applied where it's found that the displacement values and stress test are directly proportional to the flexion angle of the designed knee joint.…”
Section: State Of the Artmentioning
confidence: 99%